The 25 sitcoms that changed television : turning points in American culture - Westengard, Laura; Barlow, Aaron, 1951- (Santa Barbara, California : Praeger, 2018)
This book spotlights the 25 most important sitcoms to ever air on American television--shows that made generations laugh, challenged our ideas regarding gender, family, race, marital roles, and sexual identity, and now serve as time capsules of U.S. history. -- Provided by publisher.
What was the role of The Jeffersons in changing views regarding race and equality in America in the 1970s? How did The Golden Girls affect how society views older people? Was The Office an accurate (if exaggerated) depiction of the idiosyncrasies of being employees in a modern workplace? How did the writers of The Simpsons make it acceptable to air political satire through the vehicle of an animated cartoon ostensibly for kids? Readers of this book will see how television situation comedies have consistently held up a mirror for American audiences to see themselves--and the reflections have not always been positive or purely comedic. The introduction discusses the history of sitcoms in America, identifying their origins in radio shows and explaining how sitcom programming evolved to influence the social and cultural norms of our society. The shows are addressed chronologically, in sections delineated by decade. Each entry presents background information on the show, including the dates it aired, key cast members, and the network; explains why the show represents a notable turning point in American television; and provides an analysis of each sitcom that considers how the content was received by the American public and the lasting effects on the family unit, gender roles, culture for young adults, and minority and LGBT rights. The book also draws connections between important sitcoms and other shows that were influenced by or strikingly similar to these trendsetting programs. Lastly, a section of selections for further reading points readers to additional resources. -- Provided by publisher.
Part one: The Fifties and Sixties. I Love Lucy: An appreciation / Aaron Barlow -- The Honeymooners: American dreaming scaled down to the small screen / Martin Kich -- Leave It to Beaver: The long and memorable life of Eddie Haskell / Aaron Barlow -- Big lessons from a small town: The Andy Griffith Show / Cynthia J. Miller and Tom Shaker -- Spy versus reality: Get Smart, satire and absurdity / A. Bowdoin Van Riper -- Part two: The Seventies. The Brady Bunch: A thoroughly modern family? / Laura Westengard -- All in the Family: A sitcom about a changing America that changed America / Martin Kich -- "I'm every woman": The cultural influence and afterlife of Florence Johnston of The Jeffersons / Stacie McCormick -- Writing One Day at a Time: Reflections on a life inside the tube / Christine Tibbles McBurney -- Lights out in the newsroom: The Mary Tyler Moore Show's WJM and the decline of television news / Aaron Barlow -- Mary Hartman, Mary Hartman: The 1970s and the birth of the surreal sitcom / Jerry G. Holt -- Part three: The Eighties and Nineties. More than friendship: The Golden Girls as intentional community / Jill Belli -- Cheers: Where everybody knows your name / Michael Katims -- Feeling some type of way: Whatever happened to Murphy Brown? / Monique Ferrell -- It still matters: The Cosby Show and sociopolitical representation on television / Jacqueline Jones -- "The Reagans have had a very bad effect on you": Neoliberalism and queer possibilities in The Fresh Prince of Bel-Air / Jessica Best -- Part four: The Oughts and Teens. Nearly 30 years of "D'oh!": The animated legacy of The Simpsons / Paul Cheng -- No hugging, no learning: Seinfeld between the Yuppies and Slackers / Kevin L. Ferguson -- Ellen: American's coming out party / Laura Westengard and Aaron Barlow -- Beyond wedlock: Developing romance in Will & Grace / Emily Mattingly -- Ask and tell: Ambiguity and the narrative complexity of Sex and the City / Kimberly Hall -- The Office : Broadcast television in the digital era / Leah Shafer -- Black Lives Matter: Even in The Boondocks world / Julian Williams -- Broad City scrambles the formula / Robert Leston -- "This is what happens when they let men marry men": Assimilative politics and liberal identity in Modern Family / Laura Westengard -- Postscript / Laura Westengard and Aaron Barlow.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Situation comedies (Television programs) -- United States; Television broadcasting -- Social aspects -- United States; Comédies de situation -- États-Unis.; Télévision -- Aspect social -- États-Unis.; PERFORMING ARTS -- Reference; Situation comedies (Television programs); Television broadcasting -- Social aspects; United States